2021
DOI: 10.1111/1365-2656.13584
|View full text |Cite
|
Sign up to set email alerts
|

Implementing social network analysis to understand the socioecology of wildlife co‐occurrence and joint interactions with humans in anthropogenic environments

Abstract: 1. Human population expansion into wildlife habitats has increased interest in the behavioural ecology of human-wildlife interactions. To date, however, the socioecological factors that determine whether, when or where wild animals take risks by interacting with humans and anthropogenic factors still remains unclear.2. We adopt a comparative approach to address this gap, using social network analysis (SNA). SNA, increasingly implemented to determine human impact on wildlife ecology, can be a powerful tool to u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 86 publications
(143 reference statements)
0
14
0
Order By: Relevance
“…To capture patterns of macaque-macaque social interactions, we constructed social 'grooming networks' that linked macaques based on the proportions of time they spent engaging in grooming their conspecifics, given the extensive previous literature on the importance of grooming patterns in defining primate social structure 44,45 . In a previous study, we revealed that macaques' grooming relationships did not predict their tendencies to co-interact with humans 43 . Through this finding, we established a premise to expect that the patterning and distribution of such co-interactions with humans can be different, somewhat independent pathways for disease transmission than their social structure defined through the patterning and distribution of macaque grooming of conspecifics 43 .…”
mentioning
confidence: 73%
See 3 more Smart Citations
“…To capture patterns of macaque-macaque social interactions, we constructed social 'grooming networks' that linked macaques based on the proportions of time they spent engaging in grooming their conspecifics, given the extensive previous literature on the importance of grooming patterns in defining primate social structure 44,45 . In a previous study, we revealed that macaques' grooming relationships did not predict their tendencies to co-interact with humans 43 . Through this finding, we established a premise to expect that the patterning and distribution of such co-interactions with humans can be different, somewhat independent pathways for disease transmission than their social structure defined through the patterning and distribution of macaque grooming of conspecifics 43 .…”
mentioning
confidence: 73%
“…In a previous study, we revealed that macaques' grooming relationships did not predict their tendencies to co-interact with humans 43 . Through this finding, we established a premise to expect that the patterning and distribution of such co-interactions with humans can be different, somewhat independent pathways for disease transmission than their social structure defined through the patterning and distribution of macaque grooming of conspecifics 43 .…”
mentioning
confidence: 73%
See 2 more Smart Citations
“…From 2016 to the present day, Perc has been cited in a total of 29 publications (a few are reviewed below). Among just studies focusing on nonhuman primates, studies implementing Perc have ranged from testing phylogenetic and socioecological frameworks of primate social structure [66]; to assessing the links between dominance certainty, health and (by extension) well-being of captive macaques [35,38]; to determining the effects of rank on the socio-ecology of behavioural flexibility and risk-taking behaviours by wild primates through their interacting with humans and other anthropogenic factors [70][71][72]. Outside of nonhuman primates, Perc has also been used to generate metrics of transitivity for studies of sociality in ducks [73].…”
Section: (E) Other Applicationsmentioning
confidence: 99%